HPLC Analysis of Ceftriaxone and Ceftizoxime - Jane, Jacob; Subrahmanyam, E.V.S.; Sathyanarayana, D. (Asian Journal of Chemistry, 2010)
A rapid and simple reverse phase HPLC method has been developed and validated for the estimation of ceftriaxone and ceftizoxime. The cephalosporins were resolved on a reversephase C18 (25 x 0.46 cm i.d., 5 μm) utilizing a mobile phase of methanol and water at a flow rate of 1.0 mL min-1 and UV detection of 242 nm for ceftriaxone and 310 nm for ceftizoxime. Both cephalosporins demonstrated excellent linearity and the method of standard addition revealed recovery of 97.7-100.2%, with detection limits ranging from 1.0-1.5 μg mL-1 for both drugs. Retention time was 2.15 and 2.21 min for ceftriaxone and ceftizoxime respectively. This method was found to be a simple analytical method.